Echocardiographic follow‐up and pregnancy outcome of fetuses with cardiac asymmetry at 18–22 weeks of gestation. (29th May 2014) - Zhou, Jiawei; Zhou, Qichang; Zhang, Ming; Zeng, Shi; Peng, Qinghai; Tian, Leiqi
ABSTRACT Objective The goal of our study was to evaluate the evolution of cardiac findings and assess the pregnancy outcome of fetuses with cardiac asymmetry at midgestation. Methods We reviewed all fetuses with cardiac asymmetry at echocardiograms performed at 18–22 weeks of gestation from 2006 to 2013. The data collected included the gestational age at diagnosis, serial echocardiographic findings, karyotype testing, and pregnancy outcome. Excluded were cases of classical hypoplastic left heart syndrome (HLHS) at initial echocardiogram (i.e., aortic (AO) and/or mitral atresia or dysplasia with normal intracardiac connections), heterotaxy syndrome, twin pregnancy, fetal growth restriction, and coarctation of the aorta. Results Our study included 278 fetuses with cardiac asymmetry (defined as Z‐scores of left ventricle length or diameter of less than −2). A total of 202 (72%) fetuses had normal variations in cardiac growth by prenatal and neonatal echocardiography, 69 (25%) fetuses were confirmed to have HLHS variant by autopsy or neonatal echocardiography (with an overall survival of 4.3%), and seven (3%) fetuses were terminated before 24 weeks of gestation because of abnormal karyotypes. None of the cardiac measurements at the initial echocardiogram was significantly different between HLHS variant and normal cases. In the 69 fetuses ultimately diagnosed with HLHS variant, but not in the 202 normals, the Z‐scores of all measured left heart structures decreased progressively between the first and the last prenatal echocardiograms (P < 0.01). Conclusions The majority of the fetuses with cardiac asymmetry at 18–22 weeks have a good outcome. A minority of them progress to develop HLHS variant with advancing gestation © 2014 John Wiley & Sons, Ltd.